2012
DOI: 10.1111/j.1365-2788.2012.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrusive fathering, children's self‐regulation and social skills: a mediation analysis

Abstract: Intrusive fathering appears to carry unique risk for the development of social skills in children with DD. Findings are discussed as they related to theories of fatherhood and parenting in children with DD, as well as implications for intervention and future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 49 publications
4
42
0
3
Order By: Relevance
“…Positive association between father engagement in child development and skill acquisition was found by De Falco et al (2008) and Elder et al (2005), yet less positive results are noted elsewhere (Elder et al, 2003;Stevenson and Crnic, 2013). In reference to engagement with service providers, some fathers are presented as frustrated and angry with the educational system (Bray et al, 1995) while others positively engaged in father specific programmes (Elder et al, 2005;Vadasy et al, 1985Vadasy et al, , 1986.…”
Section: Discussionmentioning
confidence: 82%
“…Positive association between father engagement in child development and skill acquisition was found by De Falco et al (2008) and Elder et al (2005), yet less positive results are noted elsewhere (Elder et al, 2003;Stevenson and Crnic, 2013). In reference to engagement with service providers, some fathers are presented as frustrated and angry with the educational system (Bray et al, 1995) while others positively engaged in father specific programmes (Elder et al, 2005;Vadasy et al, 1985Vadasy et al, , 1986.…”
Section: Discussionmentioning
confidence: 82%
“…Most studies have not specifically examined the types of strategies that fathers use to help their toddlers regulate their emotions or pay attention. Instead, studies have looked at broad or global measures of father involvement, such as residential status or intrusiveness, and have reported associations with higher levels of self-regulation or socioemotional development (e.g., Stevenson & Crnic, 2013;Vogel et al, 2006). In a study of father-child interactions in an ethnic-minority sample, Owen et al (2013) measured father-child interaction quality and found that sensitive and stimulating fathering was a unique contributor to children's emerging response-inhibition skills.…”
Section: Fathers' Control Strategies: Links To Regulatory Skillsmentioning
confidence: 99%
“…In this way, the child's later preferences and play choices are gradually formed and are seen in the kindergarten (Carlson, 2011;Flanders et al, 2009;Stevenson, 2014). Thus, under the impact of the "gender habitus", boys prefer RTP to a greater extent than the girls and, indeed, they choose competitive power plays, whereas girls choose lighter forms of RTP (Pellegrini & Smith, 1998;Storli, 2013).…”
Section: International Research In Educationmentioning
confidence: 99%